2013
DOI: 10.1590/s1516-31802013000100024
|View full text |Cite
|
Sign up to set email alerts
|

Diastrophic dysplasia: prenatal diagnosis and review of the literature

Abstract: CONTEXT: Diastrophic dysplasia is a type of osteochondrodysplasia caused by homozygous mutation in the gene DTDST (diastrophic dysplasia sulfate transporter gene). Abnormalities occurring particularly in the skeletal and cartilaginous system are typical of the disease, which has an incidence of 1 in 100,000 live births. CASE REPORT: The case of a pregnant woman, without any consanguineous relationship with her husband, whose fetus was diagnosed with skeletal dysplasia based on ultrasound findings and DNA tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…General information: Rare form of short limbed dwarfism recognizable at birth; incidence is 1 in 100,000 live births …”
Section: Glossarymentioning
confidence: 99%
“…General information: Rare form of short limbed dwarfism recognizable at birth; incidence is 1 in 100,000 live births …”
Section: Glossarymentioning
confidence: 99%
“…Long bone shortening and hitchhiker thumbs were shown in all these cases. Details are given in Table 1 [1,3,4,[7][8][9]11]. Additional abnormalities in this case were cleft palate, micrognathia, low-set ears, small nose, and hemangioma.…”
Section: Discussionmentioning
confidence: 96%
“…The c.862 C > T (R279W) mutation is the most common mutation in Caucasians [6]. Honório et al first revealed the prenatal molecular diagnosis of diastrophic dysplasia without previous history [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the advent of prenatal molecu-lar diagnosis, there has been a reduction in diagnostic errors. 7 Antenatal diagnosis can be offered for the next pregnancy through ultrasound screening of fetus for abnormal thumb and short limbs. 15 In this report neither the parents has consanguinity nor there is history of DTD in their families.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, there were 160 Finns patients with skeletal dysplasia, while there were fewer than 300 patients in rest of the world. 7,8 Clinical presentation of this disorder may confuse with other form of dwarfism with bone disorder. Frequency of occurrence of this condition is not known in our country.…”
mentioning
confidence: 99%